CP-218 Analysis of the use of enteral nutrition monitored by pharmacists in hospital. (14th February 2016) - Lizardi, A; Zurutuza, A; Ripa, C; Ercilla, M; Gayán, MJ; Umerez, M; Urretavizcaya, M; Leunda, L; Andueza, K; Bachiller, MP
Abstract : Background: In our hospital, prescription, assessment and complication management of patients with tube feeding by enteral nutrition (EN) is made by a hospital pharmacist, who systematically monitors patients with EN. Purpose: To describe the role of a hospital pharmacist monitoring patients with EN via different types of enteral tubes and to analyse the interventions made. Material and methods: All patients (except those from the intensive care unit) were evaluated from 1 January to 31 July 2015. Data were obtained from the pharmacist´s nutritional records. Results: 49 patients, 65% men, median age 66 years (45–84), were evaluated. Diagnoses were: 11 laryngeal (22%), 7 oesophageal (14%), 7 oral (14%), 3 pharynx (6%), 2 jaw (4%) and 1 mediastinal cancer (2%), 4 swallowing disorders (8%), 3 amyotrophic lateral sclerosis (6%), 3 chylothorax (6%), 3 stroke (6%), 1 acute pancreatitis (2%), 1 pharyngocutaneous fistula (2%), 1 parapharyngeal abscess (2%), 1 intestinal (2%) and 1 oesophageal perforation (2%). Enteral access were: 20 gastrostomy (41%), 19 nasogastric tube (NGT) (39%), 3 nasojejunal tube (NYT) (6%), 3 oral (6%), 1 gastrojejunostomy (2%), 2 NGT followed by gastrostomy (4%) and 1 NGT followed by NYT (2%). The administration method used was: intermittent administration exclusively in 28 (57%); continuous tube feeding infusion exclusively in 8 (16%); in 9 (18%) intermittent was changed to continuous because of diarrhoea. 4 (8%) started continuous infusion because of tolerance problems and changed to intermittent after achieving good tolerance. Among patients with continuous infusion, EN was cyclically administered in 62%. Mean duration, volume and energy intake per day were: gastrostomy (10 days, 1462 mL, 1729 kcal); NGT (15, 1539, 1804); NYT (19, 2150, 2163); oral (7, 1583, 1583); and gastrojejunostomy (39, 750, 750). 3 (6%) required oligopeptidic EN because of diarrhoea. 25 (51%) had complications: diarrhoea 14 (29%), fullness 3 (6%), nausea 2 (4%), hyperglycaemia 2 (4%), tube output 2 (4%), aspiration 1 (2%) and obstruction 1 (2%). Conclusion: Most patients were oncologic with gastrostomy. Diarrhoea was the most common complication. It was managed by changing the administration method and EN type. Knowledge of the pharmacist about nutrition, industry prepared EN composition and management of complications improved, especially for oncologic patients with gastrostomy. No conflict of interest.